Michael Bennett : I, Michael Bennett - James Patterson; Michael Ledwidge (Michael Bennett series;, 2013)
Detective Michael Bennett takes his family to upstate New York in an effort to escape a lawless crime wave erupting in Manhattan only to find themselves immersed in another nightmare, one that endangers his relationship with his wife.